Immunisation with BCG and recombinant MVA85A induces long-lasting, polyfunctional Mycobacterium tuberculosis-specific CD4+ memory T lymphocyte populations. - Beveridge, N; Price, D; Casazza, J; Pathan, A; Sander, C; Asher, T; Ambrozak, DR; Precopio, M; Scheinberg, P; Alder, N; Roederer, M; Koup, R; et al. (2007)
In the search for effective vaccines against intracellular pathogens such as HIV, tuberculosis and malaria, recombinant viral vectors are increasingly being used to boost previously primed T cell responses. Published data have shown prime-boost vaccination with BCG-MVA85A (modified vaccinia virus Ankara expressing antigen 85A) to be highly immunogenic in humans as measured by ex vivo IFN-gamma ELISPOT. Here, we used polychromatic flow cytometry to investigate the phenotypic and functional profile of these vaccine-induced Mycobacterium tuberculosis (M.tb) antigen 85A-specific responses in greater detail. Promisingly, antigen 85A-specific CD4(+) T cells were found to be highly polyfunctional, producing IFN-gamma, TNF-alpha, IL-2 and MIP-1beta. Surface staining showed the responding CD4(+) T cells to be relatively immature (CD45RO(+) CD27(int)CD57(-)); this observation was supported by the robust proliferative responses observed following antigenic stimulation. Furthermore, these phenotypic and functional properties were independent of clonotypic composition and epitope specificity, which was maintained through the different phases of the vaccine-induced immune response. Overall, these data strongly support the use of MVA85A in humans as a boosting agent to expand polyfunctional M.tb-specific CD4(+) T cells capable of significant secondary responses.